Recent progresses in bus-ducts design. Issue 1 (4th January 2016) - Faiz, J.; Ehya, H.; Takbash, A.M.; Shojaee, S.; Hamidian, M.; Ghorbani, A.
Abstract : Purpose: – Electrical energy distribution systems must be low losses systems in order to enhance the system efficiency. Therefore, it is preferred to distribute electrical energy by bus-ducts in the place of cables over all energy levels and decrease the losses. The purpose of this paper is to focus on a comprehensive survey of various aspects of bus-ducts design including electromagnetic, mechanical and thermal. Advantages and disadvantages of different available design techniques are reviewed. Design/methodology/approach: – Different works on various bus-based power transmission and distribution systems are reviewed. Generally these are done in three categories including systems modeling methods, heat transfer in the systems, short circuit and electromagnetic force. The attempt is made to provide geometrical and materials specifications in order to present the analyzed system well. Findings: – Different types of bus-ducts from used materials, voltage level and insulation types are reviewed. Bus-duct modeling techniques are introduced which can be easily applied for bus-ducts design. Electromagnetic field distribution, thermal pattern inside and outside of the bus-duct in normal and short circuit modes and finally mechanical considerations are dominant factors which must be taken into account in the bus-ducts design. This leads to an optimal design of bus-ducts which prolong the life span of the bus-ducts fixed in the installations. Originality/value: – This paper for the first time systematically reviews the latest state of arts in the design of bus-ducts for efficient electrical energy distribution. It summarizes a variety of design techniques applicable to bus-ducts design.